Energy Efficiency and the Policy Mix - Eyre, N; Fawcett, T; Rosenow, J; Oikonomou, V (Taylor andamp; Francis (Routledge): STM, Behavioural Science and Public Health Titles, 2016)
Energy efficiency policy is expected to play a key role for meeting the European Union’s energy targets (particularly for reduced energy demand and reduced CO2 emissions) using a range of policy instrument combinations. However, most analyses undertaken so far have focused on single-policy measures rather than developing a more generic framework for assessing to what extent a particular policy mix is effective and under which specific conditions. This paper both contributes to the theoretical literature on policy mixes and undertakes an empirical analysis of the current policy mixes in buildings efficiency policy in 14 European Union countries. Building on the existing literature, and using expert knowledge, an assessment of the interaction of 55 pairs of policies is presented. This identifies policy mixes likely to deliver more, less or the same energy savings in combination than singly. The theoretical assessment is compared with actual policy mixes present within the European Union, highlighting that combinations of multiple financial incentives may need further investigation. By bringing these forms of knowledge together, the paper suggests how buildings policy mixes could be made more effective, shows gaps in current knowledge and highlights key research needs.